Síndrome de Down, doença? De quem? - Barbiero , Talia (2018)
The present article aims to analyze the ways of working with students with Down Syndrome in regular schools to understand more about this deficiency and about qualified educational approaches. For this, a large bibliographical research was done as a base method for the search of information. Among the main results found, it is necessary to consolidate and disseminate studies in the initial training stage and in the continuing training of professionals who work in a school context with these children. As evidenced by this research effort, there is a good bibliographical production about it, with some lack of pedagogical work, from early childhood to early years, a focus of our interest, but the main problem is not appropriation of existing knowledge and fact that this gap does not correspond to individual and collective investments to cure it. In this way, a half-inclusion is made, guaranteeing a school for children with Down syndrome, without the quality of the socializing and educational processes being a compromise first.